Teologi Kristen Protestan Terhadap Agama-Agama Lain di Indonesia 1966-1990 - Amos Sukamto (Religió: Jurnal Studi Agama-agama, 2019)
This paper discusses the Ecumenical Protestant-Christian theology toward other religion which is strongly influenced by the context. Sidjabat has slightly concerned about the problem of religious pluralism since inter-religious relation in his time were still relatively respectable. Victor I. Tanja paid more attention to interfaith dialogue because the Indonesian Government has been promoting a lot of interfaith dialogue and activism. Tanja is an arm of the government, in contrast to Sumartana, a theologian associated with an upsetting period where several riots, such as conflict between Christian and Muslim, raised in Surabaya, Situbondo, Tasikmalaya, Ambon and Poso. He thinks it is needed to apply on what so-called theologia religionum, theology of religions.